ANALISIS KEPUASAN PENGGUNA E-FILLING DENGAN PENDEKATAN COBRA DAN MODIFIKASINYA DI KOTA SUMBAWA BESAR - Ari, Dessanti Putri Sekti (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2022)
The purpose of this study was to determine the factors that influence the satisfaction of E-Filing users with the COBRA approach and its modifications. The variables used in this study are cost, opportunity, benefit, risk, utility, efficiency, and user satisfaction of E Filing. This type of research approach is quantitative and analyzed by multiple linear regression. This study uses primary data involving 141 respondents in the city of Sumbawa Besar. This study indicates that cost, opportunity, and utility have no significant effect on e-filing user satisfaction. Benefit and efficiency have a significant positive effect on e-filing user satisfaction. Risk has a significant negative effect on e-filing user satisfaction